Sequencing wild and cultivated cassava and related species reveals extensive interspecific hybridization and genetic diversity - Bredeson, J.V.; Lyons, J.B.; Prochnik, S.E.; Wu, G.A.; Ha, C.M.; Edsinger-Gonzales, E.; Grimwood, J.; Schmutz, J.; Rabbi, Ismail Y.; Egezi, C.; Nauluvula, P.; Lebot, V.; et al. (Springer, 2016)
Cassava (Manihot esculenta) provides calories and nutrition for more than half a billion people. It was domesticated by native Amazonian peoples through cultivation of the wild progenitor M. esculenta ssp. flabellifolia and is now grown in tropical regions worldwide. Here we provide a high-quality genome assembly for cassava with improved contiguity, linkage, and completeness; almost 97% of genes are anchored to chromosomes. We find that paleotetraploidy in cassava is shared with the related rubber tree Hevea, providing a resource for comparative studies. We also sequence a global collection of 58 Manihot accessions, including cultivated and wild cassava accessions and related species such as Ceará or India rubber (M. glaziovii), and genotype 268 African cassava varieties. We find widespread interspecific admixture, and detect the genetic signature of past cassava breeding programs. As a clonally propagated crop, cassava is especially vulnerable to pathogens and abiotic stresses. This genomic resource will inform future genome-enabled breeding efforts to improve this staple crop.